Oesophageal squamous cell carcinogenesis : a study of cell cycle regulatory proteins by immunohistochemistry - Soldin, Ryan Peter (Division of Anatomical Pathology, 2017)
Oesophageal squamous cell carcinoma (OSCC) is a highly malignant tumour that has a poor prognosis and shows marked regional variation in its incidence, implicating environmental factors. South Africa is one of several countries that has areas of high incidence. The exact aetiopathogenesis of OSCC is not well understood. Current environmental risk factors include alcohol, tobacco, human papillomavirus (HPV) infection and nutritional factors including; low intake of Vitamins A, C and riboflavin, lack of fruit and vegetables, ingestion of fungal contaminated foods and consumption of extremely hot beverages. This study was a retrospective immunohistochemical study done on paraffin embedded tissues. The histopathology, grading and staging of all resected squamous cell carcinomas over a twenty one year period from 1982 to 2002, were reviewed. Sixty eight patients were identified; all had an oesophagectomy for OSCC at Groote Schuur Hospital, a tertiary referral centre. Clinical details regarding gender, race, age, smoking or alcohol usage and survival data were collected. Survival data was updated to 23 June 2003. Two paraffin blocks representing OSCC and normal mucosa for each patient were retrieved from the archives in the Division of Anatomical Pathology. In addition, 16 cases of reflux oesophagitis were included for comparison. Initial immunohistochemical staining for HPV (Dako- clone KlH8) was undertaken but the negative results necessitated a shift in the focus of this study to that of cell cycle regulatory proteins. The tissues were evaluated for p53 (Dako - clone D0-7), p2l (Novocastro - clone 4Dl0), cyclin DI (Dako - clone DCS-6) and cyclin E (Novocastro - clone 13A3). Expression was interpreted as positive if 10% or more of the tumour cell population stained. Expression was also stratified into three levels (1, 2 and 3) depending on the percentage positive staining. Normal mucosa did not stain for any of the cell cycle regulators. OSCC stained as follows: 61.8% for p53, 27.9% for p21, 22.1 % for cyclin E and 44.1% for cyclin Dl. Reflux oesophagitis stained as follows: 31.2% for cyclin DI, 12.5% for p21 and 0% for both p53 and cyclin E. Subsequent statistical analysis failed to reveal any prognostic significance to the expression of cell cycle regulators, nor could expression or level of expression be associated with stage, grade, age, gender or alcohol use. There was however a significant relationship between cyclin DI and smoking. In addition, expression of p53 discriminated between malignant and reactive oesophageal lesions. Advancing age proved to be associated with an increased risk of mortality. Lastly, histopathological staging proved to be the most significant prognostic factor in this study.